Diversity of flesh flies (Diptera: Sarcophagidae) in an Atlantic forest fragment in Rio das Ostras, RJ, Southeastern Brazil - Morim Gomes, Marina; Antunes de Mello-Patiu, Cátia (EntomoBrasilis, 2021)
Sarcophagidae is a family of Diptera with medical-veterinary importance, which have species with sarcosaprophagous, necrophagous or causing-myiasis larvae, among others. The Brazilian state of Rio de Janeiro has 92 municipalities, but only 26 have sarcophagid records and the municipality of Rio das Ostras is one of the least registered, with only nine species recorded. This works aimed to increase the knowledge of flesh fly diversity in a conservation unit of this municipality, the “Área de Relevante Interesse Ecológico de Itapebussus”. The study was conducted in restinga and semideciduous forest. We used modified Van Someren-Rydon traps baited with decayed fish, and the samples were taken in dry and rainy seasons. A total of 446 male sarcophagines of 18 species of the genera Oxysarcodexia, Peckia, Ravinia, Sarcofahrtiopsis, and Titanogrypa were collected. We found 13 new records for the sampled municipality. The forest presented higher richness than the restinga and the most abundant species was Oxysarcodexia amorosa (Schiner). Diversity and equitability showed similar values in the two areas (H’f=2.193, H’r=2.027, J’f=0.7908 and J’r=0.7682) and the cluster analysis suggest high similarity. PERMANOVA did not present significant results for any source of variation. The presence of synanthropic and asynanthropic species in the fragment demonstrates that it is already a somewhat human-impacted environment. Marked increase in the number of sarcophagid records obtained in this small sample in the studied municipality (from nine to 22 species) shows the importance of taxonomic surveys in poorly studied areas.